2017
DOI: 10.1016/j.proci.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and control of combustion instabilities in real engines

Abstract: This is an author-deposited version published in: http://oatao.univ-toulouse.fr/ Eprints ID: 17713Open Archive Toulouse Archive Ouverte (OATAO) OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. To cite this version: AbstractThis paper presents recent progress in the eld of thermoacoustic combustion instabilities in propulsion engines such as rockets or gas turbines. Combustion instabilities have been studied for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
229
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(229 citation statements)
references
References 155 publications
(192 reference statements)
0
229
0
Order By: Relevance
“…Nevertheless, due to the flow complexity in such configurations making any precise conclusion about the evolution of entropy waves is still very difficult [30]. Further, most recent studies have shown that entropy waves do not necessarily propagate as passive scalars and can affect the base flow [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the flow complexity in such configurations making any precise conclusion about the evolution of entropy waves is still very difficult [30]. Further, most recent studies have shown that entropy waves do not necessarily propagate as passive scalars and can affect the base flow [31].…”
Section: Introductionmentioning
confidence: 99%
“…Rate of increase of pressure is defined by the speed of explosive combustion. Many experimental works [7][8][9][10][11] and works in which this process numerically is modelled [12][13][14][15][16] are devoted to studying of this question. At explosion in closed volume terminal pressure of explosion is defined by a share of the burned-down substance.…”
Section: Methodsmentioning
confidence: 99%
“…Under such conditions, the combustor suffers high-amplitude thermoacoustic limit cycles leading to high-cycle fatigue of the components and potentially to sudden mechanical failure, which must be avoided at all cost. Nowadays, it is still very difficult to predict the occurrence of thermoacoustic instabilities in real engines where the combustion system complexity is markedly increased compared to laboratory layouts [3]. The latter academic configurations nevertheless provide extremely valuable information on the fundamental features of thermoacoustic problems in practical combustors.…”
Section: Introductionmentioning
confidence: 99%